Research on Freight Locomotive Automatic Driving Based on Predictive Control - LI Cheng; ZHANG Zhengfang; SHEN Ziyang (Kongzhi Yu Xinxi Jishu)
In freight locomotive automatic driving system, it is common to encounter problems such as large following error and low parking accuracy during train operation, not only because of external interference and variable parameters, but also for inertial element and constraints in traction and braking states. It established a train operation equivalent model, studied the application of locomotive automatic driving system by model predictive control and multiple-model transformation control by fuzzy control, and presented an improved MPC method which combined with predictive control and time-delaying stability control. The proposed method has better velocity following accuracy than that of the traditional PID control, and the effectiveness of this method is proved by the simulation using measured data.